Hijras and South Asian historiography - Hinchy, Jessica (2023)
Since the 1990s, scholars of South Asia have framed the hijra community in a variety of ways, for instance, as a third gender, a transgender group, and an identity made through more than gender difference. Both interdisciplinary and historical accounts have debated the relationship between “hijra” and other gender, sexual or social subjectivities and categories. Hijra histories suggest that the community has often been at the center of historical transformations in governance, households, gender, embodiment, epistemologies, and political economies. Yet historical research has especially focused on the 19th century, raising questions about what a deeper genealogy of the term hijra might reveal about longer trajectories of historical change in gendered categories and practices. I argue that hijra histories may provide openings for gender historians to think critically about what precisely they mean by “gender.” Moreover, because hijra and transgender studies from South Asia have foregrounded the geopolitics of translation, this literature prompts fruitful questions for the field of transgender history.